Aqueous extraction from dachengqi formula granules reduces the severity of mouse acute pancreatitis via inhibition of pancreatic pro-inflammatory signalling pathways. (15th July 2020) - Ma, Xiaohua; Jin, Tao; Han, Chenxia; Shi, Na; Liang, Ge; Wen, Yongjian; Yang, Jingyu; Fu, Xianghui; Lan, Tian; Jiang, Kun; Nunes, Quentin M.; Chvanov, Michael; et al.
Abstract: Ethnopharmacological relevance: Dachengqi decoction (DCQD) belongs to a family of purgative herbal formulas widely used in China for the treatment of acute pancreatitis (AP). AP is a prevalent digestive disease currently without an effective pharmacological intervention. Formula granules have become the preferred method for delivery of herbal formulation in China given its benefit of potency retention, dosing precision and ease of use. The efficacy of DCQD formula granules (DFGs) in experimental AP models has not been investigated. Aim of the study: To analyse and compare the differences in chemical composition of DFGs, with their aqueous extraction (AE) and chloroform extraction (CE) derivatives. To assess their efficacy on severity and targeted pancreatic pro-inflammatory signalling pathways in freshly isolated acinar cells and two models of experimental AP. Material and methods: UPLC-Q-TOF-MS was used to analyse chemical components of DFGs and their extractions. Freshly isolated mouse pancreatic acinar cells were treated with taurolithocholic acid 3-sulphate disodium salt (TLCS, 500 μM) with or without DFGs, AE and CE. Apoptotic and necrotic cell death pathway activation was measured by caspase 3/7 (10 μl/mL) and propidium iodide (PI, 1 μM), respectively, using a fluorescent plate reader. Necrotic acinar cells were also counted by epifluorescence microscopy. Mice received either 7 intraperitoneal injections of caerulein (50 μg/kg) at hourly intervals or retrograde infusion of TLCS (3 mM, 50 μl) to induce AP (CER-AP and TLCS-AP, respectively). In CER-AP, mice received oral gavage of DFGs (2.1, 4.2 and 5.2 g/kg), AE (0.6, 1.2, and 2.4 g/kg) and CE (4, 9 and 17 mg/kg), or matched DFGs (1.8 g/kg) and AE (1 g/kg) for 3 times at 2-hourly intervals, or a single intraperitoneal injection of DCQD-related monomers rhein (20 mg/kg), narigeinine (25 mg/kg), and honokiol (5 mg/kg) begun at the 3rd injection of caerulein. In TLCS-AP, DFGs (4.2 g/kg) were given orally at 1, 3 and 5 h post-surgery. Disease severity and pancreatic pro-inflammatory markers were determined. Results: The main effective anthraquinones and their glycosides, flavonoids and their glycosides, polyphenols and lignans were found in the DFGs. A higher proportion of polar components including glycosides attached to anthraquinones, phenols and flavonoids was found in AE. Conversely, lower polar components containing methoxy substituted flavonoids and anthraquinones were more abundant in CE. DFGs were given at 4.2 g/kg, a consistent reduction in the pancreatic histopathology score and severity indices was observed in both CER-AP and TLCS-AP. In vitro, AE significantly reduced both apoptotic and necrotic cell death pathway activation, while CE increased TLCS-induced acinar cell necrosis. In vivo, AE at dose of 1.2 g/kg consistently reduced pancreatic histopathological scores and myeloperoxidase in the CER-AP that were associated with suppressed expression of pro-inflammatory meditator mRNAs and proteins. CE increased lung myeloperoxidase and failed to protect against CER-AP in all dosages. AE was demonstrated to be more effective than DFGs in reducing pancreatic histopathological scores and myeloperoxidase. Conclusions: AE from DFGs alleviated the severity of mouse AP models via an inhibition of pancreatic pro-inflammatory signalling pathways. Efficacy of AE on experimental AP was more potent than its original DFGs and DCQD monomers. Graphical abstract: Image 1